Questions in discourse. - Heusinger, Klaus von; Zimmermann, Malte, 1970-; Onea Gáspár, Edgar (Current research in the semantics/pragmatics interface, 2019)
The volume Questions in Discourse - Vol. 1 Semantics contains a comprehensive overview of the semantic analysis of questions and their role in structuring discourse, next to a series of in-depth contributions on individual aspects of question meanings. The expert contributions offer novel accounts of semantic phenomena such as negation and biased questions, question embedding, exhaustivity, disjunction in alternative questions, and superlative quantification particles in questions. Some accounts are modelled in the framework of inquisitive semantics, whereas others employ alternative semantics, and yet others point to the discourse-structuring potential of marked questions. All contributions are easily accessible against the background of the general introduction. Together, they give an excellent overview of current trends in question semantics.